To Remember or to Forget: Political Repression in the Collective Memory of Descendants - Inna B. Bovina; Tatiana V. Ryabova; Vladislav Y. Konkin (Peoples' Friendship University of Russia (RUDN University), 2021)
The question of political repression divides society and polarizes public discourse. Understanding political repression through the prism of socio-psychological knowledge is a zone of proximal development for researchers, because the suicidal nature of repression, which A.M. Etkind points out, makes it difficult to understand terror, hinders the work of mechanisms that operate in a society that has come into contact with a catastrophe of such magnitude and duration. The study is devoted to the study of social ideas about repression, as well as emotional reactions towards repression and the repressed among the descendants of the repressed, i.e., their children and grandchildren. A total of 110 people (61.82% - females) aged 44 to 78 years, 93.63% with higher education, participated in the study. The sample included three groups: the generation of children (21 people, M = 59.52 years; SD = 9.04); the generation of grandchildren (63 people, M = 54.71 years; SD = 7.66); and the control group (26 people, M = 53.65 years; SD = 7.72). A survey in the form of a questionnaire was used, followed by a prototypical analysis of associations, which made it possible to identify the structure of ideas about repression in the three groups. To analyze emotional reactions, a factor analysis of scores on 38 scales was carried out, followed by an analysis on the new variables. The characteristics of the structure of social representations (the core and periphery zones) are consistent with the initial hypothesis that the supposedly traumatic event of repression is perceived as a personal one by the descendants but as a social one by the respondents of the control group. There were no differences in the severity of emotional reactions in relation to the category of repressions and repressed between the generations. The combined group of descendants significantly differs from the control group in the greater severity of indicators when assessing the category of repression by the factors of Anxiety, Depression and Grief, and when assessing the category of repressed by the factor of Grief. The results of the study of social ideas about the past allow us to talk about the collective memory of repression in two generations of the descendants of the repressed: in the structure of the inner world of generations of descendants, repression is a personal event of family history, colored by sorrowful feelings of varying degrees of intensity and depth.